Search for Physics Beyond the Standard Model in Final States With a Lepton and Missing Transverse Energy in Proton-Proton Collisions at Root S = 8 Tev - Karapınar, Güler; Demir, Durmuş Ali; Karapınar, Güler; Demir, Durmuş Ali (American Physical Society, 2015)
A search for new physics in proton-proton collisions having final states with an electron or muon and missing transverse energy is presented. The analysis uses data collected in 2012 with the CMS detector, at an LHC center-of-mass energy of 8 TeV, and corresponding to an integrated luminosity of 19.7 fb(-1). No significant deviation of the transverse mass distribution of the charged lepton-neutrino system from the standard model prediction is found. Mass exclusion limits of up to 3.28 TeVat 95% confidence level for a W0-boson with the same couplings as that of the standard model W-boson are determined. Results are also derived in the framework of split universal extra dimensions, and exclusion limits on Kaluza-Klein Wd(KK)((2)) states are found. The final state with large missing transverse energy also enables a search for dark matter production with a recoiling W-boson, with limits set on the mass and the production cross section of potential candidates. Finally, limits are established for a model including interference between a left-handed W'-boson and the standard model W-boson and for a compositeness model.